Evaluation of Neoergasilus japonicus (Ergasilidae) Occurrence on Rudd Scardinius erythrophthalmus Using Fuzzy Logic Approach - (:unkn) unknown (My University, 2018)
N. japonicus is a parasitic copepod from the family Ergasilidae (Copepoda, Poecilostomatoida) and is nativeto eastern Asia. N. japonicus has spread to many countries via different reasons. The fish host of this parasitein Lake Sapanca is S. erythrophthalmus. This study proposes a decision-support tool that uses a fuzzy-logicmodel of expert knowledge to assist in multi-criteria decision-making to forecast the existence of N. japonicuson fish according to the fish size and temperature of water by using MATLAB programming language to helpthe fishery industry to detect environments suitable for procreation of the parasite. The results produced by thesoftware were compared with data obtained by parasitological examination of rudd, S. erythrophthalmus, fromLake Sapanca, Turkey. A total of 122 S. erythrophthalmus, including 64 males and 58 females with a meanlength of 24.93 ± 3.65 cm (range: 15.2–34.0 cm), were examined. The findings indicated that although thereare variations between examination results and those obtained from fuzzy software, the results are consistentwith one another. According to the results, 20.49% of the fish were infected according to the data obtainedfrom the lake. The proposed FLS system predicted that 27.87% would be infected. Hence fuzzy logic basedalgorithm make it possible to evaluate N. japonicus infection.

N. japonicus Ergasilidae (Copepoda, Poecilostomatoida) ailesinden parazit bir kopepoddur ve doğu Asya’da yaygın bir şekilde görülmektedir. N. japonicus farklı nedenlerden dolayı pek çok ülkeye yayılmıştır. Bu parazitin balık konağı Sapanca Gölün’de ki kızılkanat (S. erythrophtalmus) balığıdır. Bu çalışma, uzman bilgisi kullanarak bulanık mantık modeli oluşturup N. japonicus’un konak balıkta olma ihtimalini tahmin eden çoklu kriterler kullanan bir program sunmaktadır. Bunun için MATLAB programlama dili kullanılmış, balığın total boyu ve su sıcaklığı kullanılmıştır. Amaç, balıkçılık endüstrisinde bu parazitin üreme ihtimali olan ortamların tespit edilmesine yardımcı olmaktır. Program tarafından üretilmiş sonuçlar, Sapanca Gölü’nde kızılkanat balıkları üzerinde yapılan parazitolojik incelemeler ile karşılaştırılmıştır. Boy ortalamaları 24.93 ± 3.65 cm (aralık: 15.2–34.0 cm) toplam 122 kızılkanat (64 erkek, 58 dişi) incelenmiştir. Bulanık mantık ile üretilen sonuçlar parazitoloji incelemeleri ile ufak farklar gösterse de, içlerinde tutarlı olduğu gözlenmiştir. Sonuçların ışığında gölde incelenen balıkların %20.49’üne parazit bulaşmıştır. Sistem ise, verilere göre yaptığı tahminde bunun %27.87 olacağını öngörmüştür. Dolayısı ile bulanık mantık algoritması N. japonicus’un algılanmasını muhtemel kılabileceğini göstermiştir.
Neoergasilus japonicus (Ergasilidae) Oluşumunun Rudd Scardinius erythrophthalmus Üzerinde Bulanık Mantık Yaklaşımının Değerlendirilmesi
Keywords: Biyoloji; Matematik; İnşaat ve Yapı Teknolojisi; İnşaat Mühendisliği; Mühendislik, Elektrik ve Elektronik; Mühendislik, Makine